A tridentate phenoxy-phosphine (POP) divalent chromium complex and its reactivities in olefin polymerization. Issue 6 (24th January 2023) - Ji, Li; Song, Ping; Zhou, Youyun; Sun, Xiu-Li; Gao, Yanshan; Tang, Yong
Abstract : We reported the synthesis and characterization of a Cr(ii ) complex based on a tridentate phenoxy-phosphine ligand and studied its reactivities in ethylene and norbornene homopolymerization and ethylene copolymerization with norbornene or 1-octene. Abstract : We reported the synthesis and characterization of a Cr(ii ) complex based on a tridentate phenoxy-phosphine ligand and comprehensively studied its reactivities in ethylene and norbornene homopolymerization and ethylene copolymerization with norbornene or 1-octene. Upon methylaluminoxane (MAO) activation, the precatalyst catalyzes ethylene polymerization with activities up to 331.7 kg (mol cat h) −1 . The polyethylene (PE) M w and dispersity ( Đ ) can be flexibly tuned, ranging from predominantly high molecular weight (HMW, 42.3 kg mol −1, 97.5 wt%) to mostly low molecular weight (LMW, 1.8 kg mol −1, 94.8%), and from bimodal to nearly monomodal via changing MAO loadings and reaction temperatures. End group analysis by NMR shows β-H elimination as the major chain termination pathway vs. chain transfer to AlMe3 as a minor pathway, forming vinyl-terminated PE and saturated PE, respectively; in the cases where vinyl-terminated LMW PE is formed, vinylidene and 1, 2-substituted internal olefinic end groups can be observed at the expense of chain end vinyl and methyl groups. In norbornene homopolymerization, the catalytically active site is incapable of undergoing β-H elimination and shows single-site catalytic behavior with chain transfer to AlMe3 as the sole chain transfer/termination pathway, which is confirmed by polymer NMR and MAO loading experiments. Interestingly, the catalyst system also exhibits single-site catalytic behavior in all the ethylene copolymerization experiments with NBE and 1-octene monomers as shown by copolymer GPC and NMR ( 1 H, 13 C, DEPT, HMBC) studies, and exhibits unique monomer effects on catalytic behavior in terms of comonomer enchainment selectivity, M w, and chain transfer/termination processes. The active species under different conditions were studied by UV-vis-NIR.